2023
DOI: 10.3390/mi14061199
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Scale Tool Orientation Generation Method for Freeform Surface Machining with Bull-Nose Tool

Abstract: Free-form surface parts are widely used in industries, and they consist of intricate 3D surfaces such as molds, impellers, and turbine blades that possess complex geometrical contours and demand high precision. Proper tool orientation is crucial for ensuring the efficiency and accuracy of five-axis computer numerical control (CNC) machining. Multi-scale methods have received much attention and have been widely used in various fields. They have been proven to be instrumental and can obtain fruitful outcomes. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Once the knot vector S and control points a i have been determined, the B-spline curve P c (s) of the tool axis can be obtained from Equation (14), which is called the tool posture curve P c (s), and describes the trajectory of a particle on the spherical surface, representing the angle variation of the tool axis vector at the contact point. Therefore, new tool axis vectors are interpolated the contact point along the tool path; all tool axis vectors are located on the tool posture curve, and the global smoothing tool axis vector can be obtained.…”
Section: Anticipant Tool Orientationmentioning
confidence: 99%
See 1 more Smart Citation
“…Once the knot vector S and control points a i have been determined, the B-spline curve P c (s) of the tool axis can be obtained from Equation (14), which is called the tool posture curve P c (s), and describes the trajectory of a particle on the spherical surface, representing the angle variation of the tool axis vector at the contact point. Therefore, new tool axis vectors are interpolated the contact point along the tool path; all tool axis vectors are located on the tool posture curve, and the global smoothing tool axis vector can be obtained.…”
Section: Anticipant Tool Orientationmentioning
confidence: 99%
“…Hong et al [ 13 ] described a practical method for tool orientation generation for ball cutters commonly used in complex-surface-finish machining. Dong et al [ 14 ] proposed a multiscale tool orientation generation method that considers both the machining strip width and roughness scales. Sun et al [ 15 ] presented the prediction of an automatic tool axis orientation algorithm that avoids chatter while improving productivity.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, CAD model continuity leads to a surface deviation that can vary up to 60 µm but does not affect surface roughness [15]. Dong et al reported that the surface roughness of the freeform surface when milling is greatly influenced by the bull-nose mill's local inclination angle and tilt angle [16]. Though 3D scanning is a reliable measuring method, it requires expensive equipment.…”
Section: Introductionmentioning
confidence: 99%